Irving Layton: a canadian poet? - Almiro Pisetta (Ilha do Desterro)
Irving Layton was born near Neamtz, Roumenia, on 12 March 1912, into a Jewish family. His original name was Israel Lazarovitc, of which he decided to retain only the initials. In 1913 the family moved to Montreal, where Layton lived until 1969, when he moved to Toronto. He completed his studies at McGill University, from which he obtained a master’s degree in economics and political science in 1946. His first book of poems, Here and Now, appeared in 1945. Since then he has published about fifty volumes of poetry, ten short stories, and more than eighty articles and reviews. Recently he has published a first collection from his voluminous orrespondence. In 1983 he decided to return to his “old stumping ground” in Montreal, where his biographer, Elspeth Cameron, leaves him “fallen asleep with his knees up to his chest”(461). (As late as July 1992, Layton, almost eighty and not in good health, was still living in Montreal, well taken care of by Annette Pottier, his young fifth wife.)